Advanced nursing practice in COPD exacerbations: the solution for a gap in Switzerland?. Issue 2 (15th June 2020) - Schmid-Mohler, Gabriela; Clarenbach, Christian; Brenner, Gabi; Kohler, Malcolm; Horvath, Eva; Spielmanns, Marc; Petry, Heidi
Aim: This study aimed to address the need for adaptation of the current model of chronic obstructive pulmonary disease (COPD) care in Switzerland, particularly in regard to acute exacerbations, and how far an integrated approach involving advanced nursing practice can meet those needs. Methods: A state analysis guided by the PEPPA framework was initiated by the Pulmonology Clinic of University Hospital Zürich. Literature describing the current provision of COPD care regarding exacerbations in Switzerland and international qualitative studies describing the patient perspective were systematically searched and summarised. The health providers' perspective was investigated in three focus-group interviews. Results: A lack of systematic and state-of-the-art support for patient self-management in Switzerland was described in literature and confirmed by the health providers interviewed. While care was assessed as being comprehensive and of good quality in each individual sector, such as inpatient, outpatient, rehabilitation and home settings, it was identified as being highly fragmented across sectors. The interview participants described day-to-day examples in which a lack of support in COPD self-management and fragmentation of care negatively affected the patients' disease management. Conclusion: The necessity of coordinating the transition between healthcare sectors and self-management support and that these organisational boundaries should be addressed by a multi-professional team were identified. Initial evaluation indicates that advanced practice nurses potentially have the skill set to coordinate the team and address patients' self-management needs in complex patient situations. However, the legal foundation and a reimbursement system to ensure long-term implementation is not yet available. Advanced practice nurses have the skills to meet needs in the treatment of #AECOPD, such as transition between healthcare sectors and systematic self-management support, but the legal and financial framework is not present in Switzerland yet https://bit.ly/2wQysHV